2016
DOI: 10.1007/s12291-016-0583-8
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Angiogenesis, Proliferative Response and Apoptosis by β-Sitosterol in Rat Model of Renal Carcinogenesis

Abstract: As expanded understanding of molecular tumor characteristics, which drive renal cancer growth and progression gives a promising future for renal carcinoma therapy. The objective of the present study was designed to examine the effect of β-sitosterol on a rat model of experimental renal carcinogenesis. Renal carcinogenesis was induced in rats treated with N-diethylnitrosamine (DEN; 200 mg/kg bw single i.p., injection) and ferric nitrilotriacetate (Fe-NTA; 9 mg Fe/kg bw i.p., twice a week for 16 weeks). β-sitost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…B-sitosterol-SLN significantly inhibited the VEGF level in the serum and tissue might be due to its anti-inflammatory and antioxidant effect. In support, it was showed that b-sitosterol is an effectual VEGF suppressor in rat model of renal carcinogenesis (Sharmila & Sindhu 2017).…”
Section: Discussionmentioning
confidence: 94%
“…B-sitosterol-SLN significantly inhibited the VEGF level in the serum and tissue might be due to its anti-inflammatory and antioxidant effect. In support, it was showed that b-sitosterol is an effectual VEGF suppressor in rat model of renal carcinogenesis (Sharmila & Sindhu 2017).…”
Section: Discussionmentioning
confidence: 94%
“…β‐Sitosterol is well recognized for its therapeutic efficacy as a cholesterol‐lowering agent (total plasma cholesterol and low‐density lipoprotein) (Alphonse, Ramprasath, & Jones, ; Desai, Dong, & Miller, ) and exhibits anticancerous (Sharmila & Sindhu, ) and anti‐inflammatory activities and protection against cardiovascular diseases (Desai et al, ; Shahzada et al, ), thus being an attractive source for the development of a variety of food enriched with this sterol. In the analysis of the β‐sitosterol content as a function of each of the two independent process variables studied, similar behaviors of β‐sitosterol amount was observed for the temperature and static time (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
“…The β-sitosterol content was quantified in the oils obtained by PLE using IPA as solvent under the process conditions of the CCRD-2 and the results are shown in Table 3. The statistical analysis employed to evaluate the effect of process variables (St and T) on the content of β-sitosterol present in oils (assays 1-7; β-Sitosterol is well recognized for its therapeutic efficacy as a cholesterol-lowering agent (total plasma cholesterol and low-density lipoprotein) (Alphonse, Ramprasath, & Jones, 2017;Desai, Dong, & Miller, 2016) and exhibits anticancerous (Sharmila & Sindhu, 2017) and antiinflammatory activities and protection against cardiovascular diseases (Desai et al, 2016;Shahzada et al, 2017), thus being an attractive source for the development of a variety of food enriched with this sterol. In the analysis of the β-sitosterol content as a function of each of the two independent process variables studied, similar behaviors of β-sitosterol amount was observed for the temperature and static time (Figure 3a,b).…”
Section: Effects Of the Process Variables In The β-Sitosterol Contentmentioning
confidence: 99%
“…Furthermore, considerable interest has been developed through several animal studies dealing with the role of phytosterols in cancer protection. Ramalingam et al [43] observed that the oral administration of β -sitosterol (20 mg/kg, three times per week for 24 weeks) was associated with the inhibition of proliferation and metastasis and the induction of apoptosis in renal cancer cells in rats. Similar results have also been observed in other animal experiments, which confirmed the antitumor effects of high intakes of phytosterols [44–48].…”
Section: Discussionmentioning
confidence: 99%